Digital main line system of numerical control machine tool - YAN MAN; HUANG CHANG; YANG HUABIN; YANG JIANZHONG; XIA HUANYU (2025)
The invention discloses a numerical control machine tool digital main line system, and relates to the technical field of numerical control machine tool data acquisition and management, and the numerical control machine tool digital main line system comprises an assembly data entry module, a debugging data entry module, a compensation data entry module, a periodic physical examination data entry module and a digital main line database; the assembly data input module inputs and stores the assembly data of the numerical control machine tool, and uploads the assembly data to the digital main line database; the debugging data input module inputs and stores debugging data and uploads the debugging data to the digital main line database; the compensation data input module inputs and stores compensation data and uploads the compensation data to the digital main line database; the periodic physical examination data input module inputs and stores periodic physical examination data of the numerical control machine tool